STRATEGI PEMASARAN DAUN TALAS BENENG (STUDI KASUS KELOMPOK TANI TALAS DI KECAMATAN JUMO) - Said Bambang Nurcahya; Octaviani Ratna Sari Santoso (Universitas Nurtanio Bandung, 2023)
22 Farmer groups in Jumo District, Temanggung Regency are currently shifting to beneng taro cultivation, collectors and buyers who come to receive the best quality dried taro leaves at a price of IDR 20,000 (twenty thousand rupiah). One farmer group consists of 20 - 30 taro farmers with a total garden area of ​​14 hectares. Taro belongs to the tuber family, tubers, stems and leaves can be processed into food, medicine and the leaves can be used as a substitute for tobacco leaves as raw material for cigarettes. The obstacle experienced by farmers in beneng taro cultivation is in determining the selling price, especially for mass sales, in this case the taro leaf harvest can be picked once every three months and can be planned every two weeks, due to the nature of taro which grows and develops throughout the year and not too affected by the season, the farmers in Jumo District, Temanggung Regency make taro as an alternative when the tobacco plant is not in the growing season. In this case the author does community service in helping to determine the selling price and bring together buyers/exporters who receive crops with a contract quantity of 8 tons/month. Of course there were many obstacles at the beginning of this service, for this reason, initially a marketing analysis was carried out, followed by cultivation guidance, and standard equipment/machines for processing taro leaves so that the best quality produced was sold at better prices, access to exporters or even overseas buyers was The main objective of this study, while the methodology used in this study is to use descriptive analysis with the conclusion that the cost of goods manufactured and the break-even price are the main factors in determining the selling price and determining the profits of all members of the taro beneng farmer group.